IMPLIKASI PERUBAHAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 MENJADI UNDANG-UNDANG NOMOR 16 TAHUN 2016 TENTANG BATASAN USIA PERKAWINAN PERSPEKTIF HADIST - Falih Aqil, Irfan (Al-Usroh : Jurnal Hukum Keluarga Islam, 2025)
This study discusses the implications of changing Law Number 1 of 1974 to Law Number 16 of 2019 related to the age limit for marriage, reviewed from the perspective of the hadith of the Prophet Muhammad ﷺ. This change shows the state's commitment to reducing the rate of early marriage and ensuring the physical and psychological maturity of the bride-to-be. This research uses a descriptive qualitative method with a normative and sociological approach, through a study of regulations and sahih hadiths about the recommendation of marriage for youth. The results of the analysis show that both the hadith and the provisions of the law emphasize the importance of physical, mental, and financial readiness in marriage. Although the sharia does not stipulate a numerical age, the principle of "who is able should marry" in the hadith is in line with the age limit of 19 years in Law No. 16 of 2019. This research emphasizes that harmonization between religious norms and state laws is an important step in building healthy, religious, and dignified families.